Value of Dual-energy Lung Perfusion Imaging Using a Dual-source CT System for the Pulmonary Embolism - Zhang Jinshan; Cai Jing; Liu Shulan; Zhang Xianmei (Open Life Sciences, 2018)
To investigate the diagnostic value of dual-energy lung perfusion imaging (DEPI) using a dual-source CT system for the pulmonary embolism (PE).